2014
DOI: 10.5897/ajar2013.7973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulphur on yield and chemical composition of essential oil of Ocimum basilicum L.

Abstract: This study aimed at assessing the effect of using different sulphur dilutions in the yield and composition of essential oil of Ocimum basilicum L. (basil). Sulphur was applied at different dilution rates with a centesimal scale ranging from 0c (control), 6c, 12c, 24c, to 30c. The experiment was conducted in pots at open atmosphere for 5 months, using a weekly dosage of 250 ml of the different dilution rates. Parameters evaluated were: Yield of essential oil by hydrodistillation (g%) and chemical composition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(16 reference statements)
1
1
1
Order By: Relevance
“…Increased growth and development in plants fertilized with higher concentrations of macronutrients or inoculated with PGPR have been reported for several species (Egamberdieva and Teixeira da Silva, 2015;Orhan et al, 2006;Fan et al, 2017). The data obtained displayed that the effects of nitrogen and sulfur fertilization on sweet basil are consistent with previous reports with fresh biomass showing an increasing trend as determined by micronutrients supplementation (Zheljazkov et al, 2008;Kiferle et al, 2011;Oliveira et al, 2014). Indeed, N fertilization has already been shown to be one of the pivotal factors affecting basil yield (Zheljazkov et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Increased growth and development in plants fertilized with higher concentrations of macronutrients or inoculated with PGPR have been reported for several species (Egamberdieva and Teixeira da Silva, 2015;Orhan et al, 2006;Fan et al, 2017). The data obtained displayed that the effects of nitrogen and sulfur fertilization on sweet basil are consistent with previous reports with fresh biomass showing an increasing trend as determined by micronutrients supplementation (Zheljazkov et al, 2008;Kiferle et al, 2011;Oliveira et al, 2014). Indeed, N fertilization has already been shown to be one of the pivotal factors affecting basil yield (Zheljazkov et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…Genovese. Although Oliveira et al (2014) reported that S fertilizer increased biomass production only at the root level, in the present study, shoot biomass of cv. Genovese is also increased.…”
Section: Discussioncontrasting
confidence: 71%
“…Composition of Urea fertilizer 80% + ZA 20% and the frequency of fertilization every one week gave the highest effect on the fresh and dry weight of rootsshoots (Table 5). The growth of basil plants can be increased by providing fertilizers that have the perfect balance of Nitrogen and Sulphur (N:S) (Oliveira et al, 2014). Zenda et al (2021) mentioned that the optimum ratio of nitrogen and sulfur in the soil was 7:1.…”
Section: Plant Growth (First Study)mentioning
confidence: 99%